Photobiomodulation in clinical practice - Stefano Bacci; Franco Bassetto; Alessandro Corsi; Ornella Forma; Vieri Grandi; Alberto Macciò; Antonio Raspa; Carlotta Scarpa; Gregorio Stratta; Mirko Tessari (Veins and Lymphatics, 2023)
For the past few years, we have been witnessing a gradual, but rapid change in the management of skin wounds: the so-called 'advanced' dressings have been joined, and partly replaced, by interactive dressings, in which the dressing itself interacts with the wound bed and perilesional skin, modulating one or more aspects of the tissue repair mechanism through the interaction with cells, chemical mediators and factors hindering healing. The even more recent introduction of high-tech devices has definitively propelled Wound Care into the modern era of Tech Treatment, in which one or more technologies are employed in the management of the wound and the reparative process.